Keharmonisan Keluarga Wanita Karier Di Kelurahan Padangmatinggi Lestari - Asnah Asnah (Jurnal Kajian Gender dan Anak, 2020)
The plunge of women in the world of work creates new problems, where working-women escpecially housewives will be time-consuming for the family, this creates problems with family harmony. On the basis of the above problems, this study wants to know how to empower women, why women want to work, is not a problem for the harmony of their family. This research was carried out in the Padangmatinggi Lestari village with a qualitative approach. The instruments used were observation sheets and interviews, where the subjects used as informants were mothers who worked as teachers, midwives and employees. Then analyze it using longwe analysis. Based on the data obtained it can be concluded that the empowerment of career women seen from welfare has been able to improve family welfare, but its awareness of gender roles and access is still limited as well as its power in making decisions still dominated by men (husbands). This is in line with the motivating factors for women to work, generally to improve the family economy, not because of awareness of their rights as women. Based on the criteria included in the theoretical study and the results of interviews with informants, it can be said that the families of career women in the Padangmatinggi Lestari village are categorized as prosperous families